WAR CRIMES AGAINST THE ENVIRONMENT: PROBLEMS OF QUALIFICATION (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to establishing the features of the elements of war crimes against the environment, identifying the problem of their qualification. It is found that both international and national criminal law require a rational change in the focus of regulatory efforts from anthropocentrism to ecocentrism where there is a need for criminal legal protection of the environment regardless of people. It is proved that changing the concept in this way in the legal assessment of criminal damage to the environment, including and in particular in the context of armed conflict, allows qualifying the relevant actions precisely as war crimes without reference to the threat to the life and health of the population. It is proposed to supplement the disposition of Part 1 of Article 438 of the Criminal Code of Ukraine with an alternative act as part of war crimes of the following content: “…causing damage to the natural environment not justified by military necessity or disproportionate to a legitimate military objective…”. The need to expand the scope of documentation and investigation of war crimes against the environment at the expense of those of them that consist in violations of restrictions and prohibitions provided for by international humanitarian law in the sphere of the use of natural resources within the framework of ensuring the occupation regime has been proven.
Keywords: armed conflict; war crime; composition of the crime; international humanitarian law; environment; natural environment; contextual element; occupation; qualification